Haematobiochemical changes and enterc pathology of spontaneous canine parvovirus infection - SINGH, K P; SINGH, R; SINHA, D K; CHAUHAN, R S (The Indian Journal of Animal Sciences, 2011)
The outbreaks of canine parvovirus infection \vere recorded in 2 organized kennels of paramilitary forces in Apri12005: 5 out of 41 (12%) and 3 out of 9 (330/0) pups of 3-5 months age were died in 2 separate disease outbreaks with haelTIOrrhagic enteritis..Microscopic exatnination revealed stunted villi and hypertrophic disorganized lining epithelial cells with presence of intranuclear inclusion bodies in crypts.Â